KEKUATAN ALAT BUKTI VISUM ET REPERTUM DALAM MENJATUHKAN PIDANA TERHADAP PELAKU PENCABULAN ANAK (STUDI KASUS NOMOR 123/PID.SUS/2020/PNOLM): KEKUATAN ALAT BUKTI VISUM ET REPERTUM DALAM MENJATUHKAN PIDANA TERHADAP PELAKU PENCABULAN ANAK (STUDI KASUS NOMOR 123/PID.SUS/2020/PNOLM) - doni; Hernawati RAS; Thariq Muslim; Dhea Alfie; Ery Firsanti; Hodijatussolihah (Jurnal Media Justitia Nusantara, 2025)
“Visum et repertum is an important piece of evidence in the criminal justice system, especially in cases of child sexual abuse. This study examines the strength of visum et repertum as evidence in the criminal trial of child abuse offenders, referring to case study number 123/PID.SUS/2020/PNOLM. The method employed in this research is a normative legal approach, aiming to identify and analyze the role of visum et repertum as evidence in prosecuting child abuse offenders. This research utilizes primary legal materials, such as laws and court decisions, as well as secondary legal materials, including literature, doctrines, and expert opinions regarding the application of visum et repertum in sexual violence cases. The findings indicate that visum et repertum plays an essential role in supporting the charges against the child abuse offender, although in some cases, it cannot stand alone as conclusive evidence. Visum et repertum often serves to reinforce witness testimony or other evidence in the judicial process. The study also finds that while visum et repertum can make a significant contribution to the proof, it must be integrated with other evidence to ensure a lawful and fair conviction. Therefore, the role of visum et repertum as evidence should be carefully considered in every criminal trial”.